Cost comparisons of available brands of insulin glargine preparations - Rajadnya, Vikram Anant; More, Diya Amol (International Journal of Basic & Clinical Pharmacology, 2021)
Background: The objective was to study the annual cost of each of the four important brands of insulin glargine available in India and to study the comparative annual cost of all the four brands. Methods: Four most commonly prescribed brands of insulin glargine vials were selected for cost comparisons. The daily as well as annual cost of prescription of insulin glargine vials based on once daily use was worked out directly as well as in percentages and presented in the form of table and bar diagrams. Results: After careful analysis of the data it was found that the costliest brand, brand D is more than two times costlier than the cheapest brand, brand B and thus the brand preparation selection, can lead to huge difference in annual cost burden to the patient. Conclusions: This significant cost difference between costliest and cheapest brands of insulin glargine vials assumes even further importance since majority of the diabetics need to bear the cost of multiple drugs prescribed to them, on their own. Thus it rather becomes a duty of the prescribing health care provider to prescribe those medicines which are cost effective to his/her patients.